The Thermal State and Interior Structure of Mars. Issue 22 (28th November 2018) - Plesa, A.‐C.; Padovan, S.; Tosi, N.; Breuer, D.; Grott, M.; Wieczorek, M. A.; Spohn, T.; Smrekar, S. E.; Banerdt, W. B.
Abstract: The present‐day thermal state, interior structure, composition, and rheology of Mars can be constrained by comparing the results of thermal history calculations with geophysical, petrological, and geological observations. Using the largest‐to‐date set of 3‐D thermal evolution models, we find that a limited set of models can satisfy all available constraints simultaneously. These models require a core radius strictly larger than 1, 800 km, a crust with an average thickness between 48.8 and 87.1 km containing more than half of the planet's bulk abundance of heat producing elements, and a dry mantle rheology. A strong pressure dependence of the viscosity leads to the formation of prominent mantle plumes producing melt underneath Tharsis up to the present time. Heat flow and core size estimates derived from the InSight (Interior Exploration using Seismic Investigations, Geodesy and Heat Transport) mission will increase the set of constraining data and help to confine the range of admissible models. Plain Language Summary: We constrain the thermal state and interior structure of Mars by combining a large number of observations with thermal evolution models. Models that match the available observations require a core radius larger that half the planetary radius and a crust thicker than 48.8 km but thinner than 87.1 km on average. All best‐fit models suggest that more than half of the planet's bulk abundance of heat producing elements is located in the crust. Mantle plumes may still be active today in the interior of Mars and produce partial melt underneath the Tharsis volcanic province. Our results have important implications for the thermal evolution of Mars. Future data from the InSight (Interior Exploration using Seismic Investigations, Geodesy and Heat Transport) mission can be used to validate our models and further improve our understanding of the thermal evolution of Mars. Key Points: We combine the largest‐to‐date set of 3‐D dynamical models with observations to constrain the thermal state and interior structure of Mars Best‐fit models suggest a core radius strictly larger than 1, 800 km and an average crustal thickness 48.8 km < d c < 87.1 km Models suggest a large pressure dependence of the viscosity and a crust containing 65‐70% of the total amount of heat producing elements